Stencil printed liquid metal based micron-sized interconnects for stretchable electronics. (2023) - Kumar Sarkar, Sudipta; Parameswaran, Chithra; Maji, Debpratim; Gupta, Dipti
Abstract: Eutectic gallium indium (E-GaIn) alloy based liquid metal is considered to be a promising material for manufacturing interconnects in stretchable electronics based applications due to its high electrical conductivity and inherent mechanical deformability. The current work demonstrates an easy and single step method of fabricating micron-sized (the width of ~ 200 μm) highly conducting stretchable interconnects by stencil printing of E-GaIn on stretchable polydimethylsiloxane (PDMS) substrate. The obtained stretchable pattern showed excellent electrical and mechanical property by exhibiting a low average resistance value of ~ 6.5 O even at elongation up to 50%. Moreover, it showed superior stability against stretching cycles with just ± 0.12 Ω of variation in resistance. A commercial light emitting diode was mounted on the patterns and illuminated to describe the role of interconnects in a realistic circuit.